Personalised medicine in hypercholesterolaemia: the role of pharmacogenetics in statin therapy. (16th November 2020) - Ahangari, Najmeh; Doosti, Mohammad; Ghayour Mobarhan, Majid; Sahebkar, Amirhossein; Ferns, Gordon A.; Pasdar, Alireza
Abstract: Statins are the first-line choice in Lipid-lowering therapy to reduce cardiovascular risk. In a continuous attempt to optimise treatment success, there is a need for additional research on genes and related molecular pathways that can determine the efficacy and toxicity of lipid-lowering drugs. Several variations within genes associated with lipid metabolism, including those involved in uptake, distribution and metabolism of statins have been reported. The purpose of this study was to evaluate the effect of genetic variations in the key genes responsible for statins' metabolism and their role in personalised medicine and pharmacogenetic testing (PGx) in patients treated with such drugs. Genetic assessment for specific known SNPs within the most known genes such as ABCG2, SLCO1B1, CYP3A4, and HMGCR, appears likely to predict the efficacy of statin therapy and prevent their side effects but does not necessarily reduce the risk of cardiovascular events. Key Messages: Hypercholesterolaemia patients show different response to statin therapy. Several variations within genes associated with statin metabolism have been investigated. Genetic assessment for specific known SNPs within the most known genes may improve the efficacy of statins treatment and prevent their side effects.